(untitled) (Hekima Review, 2008)
The existence of ‘African theology’ is no longer a subject of debate. This article reviews the content and perspectives of African theologians, particularly those from East Africa. It examines the positions of these theologians on issues of culture, modernity and the public sphere. On the whole, it recognises a certain romanticisation of the African past and an unconvincing dismissal of some positive contributions of modernity to the African civilisation.